Protection of social rights of military personnel in the procedure of administrative proceedings - Teremetskyi, Vladyslav; Rusnak, Lesya (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
The scientific article is devoted to the problems of social protection of the rights of military personnel in the order of administrative proceedings. Legislative acts and individual court decisions of cassation instance courts in typical cases were studied. The scientific developments of researchers regarding protecting military personnel's rights in judicial and administrative procedures have been studied.It is claimed that the protection of the rights of military personnel in the administrative proceedings is the procedure for filing and considering an administrative claim of a military personnel in court in the administrative proceedings provided for by the Code of Administrative Proceedings of Ukraine. Specific features of consideration of such disputes in the order of administrative proceedings are defined. It is emphasized that the burden of proof in such disputes rests with the authorities whose decision is contested by the military personnel. The case can be recognized as typical and decided based on a model decision of the Supreme Court. The plaintiff may file an administrative claim with the court which is located at his place of residence. The plaintiff may be exempted from paying the court fee. The case can be considered in the order of simplified or written proceedings.Recommendations have been developed for plaintiffs in cases on the protection of social rights of military personnel. It is proposed to apply the provision of evidence together with the administrative lawsuit, in which the court is asked to demand from the military units in which the plaintiff served all the documents related to the calculation of financial support, which is required for the calculation of different types of social benefits. It is proposed that a motion for a forensic medical examination be filed in the court process. The purpose of the expert investigation may be to confirm the reasons for the establishment of disability as a result of wounds and injuries received during military service.